Describing and Valuing Learning: Proposals and Experiences from STEM - Daniela Lazzaro; Alessia Brunetta (Pensa MultiMedia, 2022)
This article presents some thoughts concerning the competence "Analyse and interpret data and draw appropriate conclusions" and to the way STEM could contribute to such competence. The fieldwork of reference is that of an Italian Lower Secondary School. Investigative questions bear on the way the ability to interpret data and information is developed, the way such ability is used to draw conclusions, and the nature of the processes enacted by students in this sense. Furthermore, during the design of teaching activities, it emerged how important it is to identify links and shared processes between different STEM subjects, as well as the need to adopt appropriate instruments to observe and assess competence.